Democracia e socialismo nos debates do Partido dos Trabalhadores (1987-1991) - Silva, Felipe Henrique Gonçalves da (2012)
This dissertation analyzes the formation and development of the political thought of the Workers Party (Partido dos Trabalhadores - PT) between the years 1987 to 1991. It seeks to understand the debates about the categories of democracy and socialism and, therefore, the appropriation of the notion of democracy as a universal value, from a eurocomunist reading of the main theses and categories of the Italian Marxist Antonio Gramsci. It analyzes the discussions of concepts such as mass party, state, accumulation of power, hegemony, real socialism and democratic socialism". In this investigative path, we studied magazine articles from Teoria e Debate (Theory and Discussion) and political resolutions of Meetings and National Congresses, both official documents of the Workers Party (PT). Still looking to grasp the historical process of formation of the PT theory taking into account their relationship with both the Brazilian left which emerges, as with the character of the "democratic left" in the world as a whole. In this way we can note that PT, despite of being proposed as a "new historical", itself engenders the same problems that agonized left in its history, considering that by rejecting to undertake a deep theoretical analysis of reality, PT becomes the victim of electioneering practices and proposals for better ways of administering the capital, in the speech program for economic growth and income distribution. The fall of the Berlin Wall and the collapse of "real socialism" consolidated a process of abandonment of Marxist theories and definition of "democratic socialism", in other words the option for the defense of "democratic path to socialism" emphasizes the centrality of the passage from work, typical of Marx's ontology, to the centrality of politics. In this change, Marxist references have been definitely abandoned, the ones which still hovered and, instead, they feature post-modern and liberal features. We found during the research appropriations issues about the main theses of Karl Marx. We seek from the Marxian legacy show the limits of political democracy as the ultimate form of freedom, because it rests on pillars of society ruled by capital. By demonstrating the negative nature of politics, we evidenced by the Marxist bringing in order to overcome the politics and the capital in favor of the human emancipation